A new species of Limnonectes (Amphibia: Anura: Dicroglossidae) from Vietnam - Pham, Cuong The; Le, Minh Duc; Ngo, Hanh Thi; Ziegler, Thomas; Nguyen, Truong Quang (Zootaxa, 2018)
A new species of Limnonectes from central Vietnam is described based on morphological and molecular differences. Morphologically, the new species is distinguishable from its congeners on the basis of a combination of the following diagnostic characters: SVL 47.5–60.9 in males, 42.3–51.1 mm in females; males with moderately enlarged head (HL/SVL 0.48), head longer than wide; vomerine teeth present; external vocal sacs absent; rostral length short (RL/SVL 0.14 in males, 0.15 in females); tympanum invisible; dorsal surface of head, body, and flanks smooth; dorsal surface of tibia and foot distinctly tuberculate, covered with moderately dense, small, low tubercles; supratympanic fold present; dorsolateral fold absent; toes webbed to posterior of terminal phalanx; in life, dorsum with light yellowish brown markings, throat and chest white with brown markings, and ventral surface of abdomen white or white with brown markings. In phylogenetic analyses, the new species is the sister taxon to an undescribed species from Cambodia.